Comparison of Results Between Patients Who Received Warfarin in Chaiyaphum Hospital and Rural Hospitals in Chaiyaphum Province - ภัทรพงศ์สินธุ์, มรกต (Journal of Preventive Medicine Association of Thailand, 2019)
The objective of this study is to compare the results of treatment in patients receiving Warfarin in Chaiyaphum Hospital with those in rural hospitals in Chaiyaphum Province. The samples are patients receiving Warfarin in Chaiyaphum Province during the period from October 1, 2013 to September 30, 2014. There were 1,277 patients receiving Warfarin in Chaiyaphum Province. The tool of this study was a record form that composed of general data and results of treatments. The form was approved for accuracy by epidemiology experts. Data was collected from medical record and drugs profile of patients receiving Warfarin in Chaiyaphum Province. Results of treatments were analyzed using descriptive statistics such as percentage, mean, standard deviation and independent t-test. The numbers of patients receiving Warfarin were 1,277 patients per year, 571 patients per year were treated in Chaiyaphum Hospital, and 706 patients per year were treated in rural hospitals. INR was performed 3,758 times a year in Chaiyaphum Hospital and 3,578 times a year in rural hospitals. The results of this study were patients receiving Warfarin in rural hospitals in Chaiyaphum Province had mean of stroke event 1 time/year and loss follow up 58 times/year less than patients receiving Warfarin in Chaiyaphum Hospital 6 times/year and 341 times/year. The statistical analysis showed stroke event and loss follow up was significantly different. Results of treatments at rural hospitals and Chaiyaphum Hospital were INR in target 2,006 times/year and 2,088 times/year, major bleeding 3 times/year and 21 times/year, minor bleeding 150 times/year and 89 times/year, and death 25 atients/year and 46 patients/year. So there are not significantly different between rural hospitals and Chaiyaphum hospital. To take care of patients receiving Warfarin by Warfarin clinic and network in rural hospitals can decrease complications and increase the accessibility of medical service. Warfarin clinic and network should be continued and extended.